Influence of sodium borate on the early age hydration of calcium sulfoaluminate cement. (April 2015) - Champenois, Jean-Baptiste; Dhoury, Mélanie; Cau Dit Coumes, Céline; Mercier, Cyrille; Revel, Bertrand; Le Bescop, Patrick; Damidot, Denis
Abstract: Calcium sulfoaluminate (CSA) cements are potential candidates for the conditioning of radioactive wastes with high sodium borate concentrations. This work thus investigates early age hydration of two CSA cements with different gypsum contents (0 to 20%) as a function of the mixing solution composition (borate and NaOH concentrations). Gypsum plays a key role in controlling the reactivity of cement. When the mixing solution is pure water, increasing the gypsum concentration accelerates cement hydration. However, the reverse is observed when the mixing solution contains sodium borate. Until gypsum exhaustion, the pore solution pH remains constant at 10.8, and a poorly crystallized borate compound (ulexite) precipitates. A correlation is established between this transient precipitation and the hydration delay. Decreasing the gypsum content in the binder, or increasing the sodium content in the mixing solution, are two ways of reducing the stability of ulexite, thus decreasing the hydration delay.